Sickle Cell Anemia Screening in Newborns and Analysis of Haplotypes in Patients from Santiago Island, Cape Verde - Ariana Freire; Laura Charola-Ramos; Elisa González-Guerra; João Gonçalves; Vanusa Rocha; Vera Afreixo; Enrique Martínez-Carretero; José M. Raya (Anemia)
Sickle cell anemia (SCA) results from a mutation in the β-globin gene, leading to the production of mutant hemoglobin, known as hemoglobin S (HbS). Despite being a genetic disorder, the phenotype of SCA can be influenced by the level of fetal hemoglobin (HbF), which is associated with beta S-globin haplotypes. In this study, we conducted newborn screening (NBS) using samples collected from umbilical cord blood in two hospitals on Santiago Island, Cape Verde. In newborns, HbS was detected using high-performance liquid chromatography (HPLC) on dried blood spot, with confirmation through polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP). In addition, we assessed the hematological and clinical characteristics of a second population group consisting of patients diagnosed with SCA. Haplotype determination was performed on both newborns with HbS and patients with SCA. Beta S-globin haplotypes were determined using PCR-RFLP. Hematological values were analyzed using standard methods. Out of 346 newborns, 21 (6%) were carriers of the sickle cell trait (HbAS) while none were identified as homozygous for sickle cell disease (HbSS). Among both groups of individuals, four haplotypes were identified: Senegal, Arabi-Indian, Bantu, and Benin. The Senegal haplotype was the most prevalent, possibly reflecting the ethnic origin of the mutations observed. Hematological values did not differ significantly among haplotypes. However, higher levels of HbF were associated with better hematological values. These findings suggest a positive impact of elevated HbF levels on reducing the severity of SCA. Finally, we demonstrated how the combination of technics, HPLC and molecular analysis, provided a consistent and reproducible results that can be used for NBS for SCA.